Efikasi Diri, Perawatan Diri Asupan Cairan, Peningkatan Berat Badan Intradialisis Klien Hemodialisis - Handono Fatkhur Rahman; Nadiatus Sholihah; Setiyo Adi Nugroho (Jurnal SainHealth, 2019)
Increased intradialysis weight gain increases the risk of cardiovascular death. Limiting fluid intake was very important to do because the kidneys cannot function normally. An increased intradialysis weight gain over 5% of dry weight can cause any complication. An internal factor that affects a person in performing self-care on fluid intake restriction, in this case is self-efficacy. The purpose of this study to determine the relationship of self-efficacy and self-care fluid intake with increased intradialysis weight gain. This research is a quantitative research, with cross sectional approach. Number of samples selected with random sampling was 112 respondents, primary data collection with questionnaires and weight scale. Statistical analysis used pearson product moment and multiple linier regression. The result of pearson product moment analysis shows p-value of self-efficay was 0,000 and p-value of self-care fluid intake was 0,038 means that each variables has a statistically significant relationship with increased intradialisis weight gain. The result of multiple linier regression analysis shows coefficient of determination value 0,138, means 13,8% self-efficacy and self-care fluid intake variables determine increased intradialysis weight gain, while 86,2% is determined by other variables not included in this research. Conclusion from this research is there is relationship between self-efficacy and self-care fluid intake to increased intradialysis weight gain with negative correlation coefficient, Means the stronger self-efficay and the better behavior of self-care fluid intake of hemodialysis clients will decrease the increase in intradialisis weight gain.